Leader-member exchange and individual performance. The meta-analysis = Wymiana LMX a zachowania indywidualne pracowników. Metaanaliza - Mazur, Karolina (Zielona Góra: Faculty of Economics and Management Press)
The paper contents the meta-analysis of 56 studies published in 47 scientific papers. The intercorrelations between Leader-Member Exchange and Individual Performance and Organizational Citizenship Behavior has been examined. The meta-analysis confirmed the correlation between those variables.
Keywords: wymiana społeczna; indywidualna wydajność pracy; zachowania etosowe; metaanaliza; Leader-Member Exchange; individual performance; organizational ctizenship behavior